Peri-Operative Use of Transexamic Acid in Reduction of Post Operative Seroma Formation in Patients Undergoing Ventral Hernia Repair - Farah Batool Siddiqui, Farooq Umer, Taha Junaid, Muhammad Ameer Hamza, Muhammad Maazullah Khan, Syed Tahir Rasool Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To examine the efficacy of Intraoperative and postoperative IV transamine, in reducing postoperative seroma formation in patients undergoing ventral hernia repair. Study Design: Randomized controlled clinical trial Study place: Karachi Methodology: Eighty patients filled out the in-depth age, gender, and body mass index (BMI) registration forms. All of the patients ranged in age from fifteen to sixty. Patients were randomly assigned to either Group A (receiving 1 g of tranexamic acid Intraoperative and 500mg tranexamic acid 12 hours apart daily for 2 postoperative days) or Group B (not receiving any drug during or after surgery). Drainage volume was collected at postoperative day 1, 2, 3, 4, and 5 was recorded and were compared in both groups. Results: The Mean±S.D of age of the participants in both groups were 41.5± 9.9 and 42.75±9.7 years. Group A had 20% males and 80% female, while group B had 22% males and 78% females. The Mean±S.D of BMI of the participants in both groups were 26.8±3.4 and 25.3± 4.4kg/m2. A significant difference in the drainage volume between group A and B was observed at 1st (0.025), 2nd (0.001), 3rd (0.004) and 4th (0.003) day were observed. Practical implication: This study will help to determine how tranexamic acid is useful in reducing seroma after hernia repair Conclusion: Seroma development after ventral hernia surgeries may be minimized with the use of tranexamic acid. Keywords: Hernia, tranexamic acid, clinical trial, seroma, effectiveness, hernia repair